Tìm x: 4896 – x = 231
A. 4566
B. 4655
C. 4665
D. 4656
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a) – 1 < x < 49 18 => x ∈ {0;1;2}
b) − 1 24 < x 24 < 1 14 => x = 0
c) 2 3 ≤ x ≤ 26 5 => x ∈ {1;2;3;4;5}
d) 0 < x ≤ 1 => x = 1
a: (x+1)+(x+2)+...+(x+98)=4655
=>(x+x+...+x)+(1+2+...+98)=4655
=>\(98x+98\cdot\dfrac{99}{2}=4655\)
=>\(98x+4851=4655\)
=>\(98x=-196\)
=>x=-2(loại)
b: -83-(x+15)=-20
=>83+(x+15)=20
=>x+98=20
=>x=20-98=-78(loại)
a. 191 275 + 646 372 = 837 647
b. 97 988 – 58 437 = 39 551
c. 126 x 312 = 39 312
d. 4 896 : 72 = 68
a. 646 372 + 191 275 = 837 647
b. 96897 – 59346 = 37 551
c. 312 x 126 = 39 312
d. 4 896 : 68 = 72
a, (9.x-21) : 3 = 2
=>9x-21=6
=>9x=27
=>x=3
b, (x-39)-21=0
=>x-39-21=0
=>x-60=0
=>x=60
c, 231+(312-x)=531
=>231+312-x=531
=>543-x=531
=>x=543-531
=>x=12
d, 53.(9-x)=53
=>9-x=1
=>x=8
a/ \(\frac{\left(9x-21\right)}{3}=2\)
\(\Rightarrow9x-21=2\cdot3=6\)
\(\Rightarrow9x=6+21=27\)
\(\Rightarrow x=\frac{27}{9}=3\)
b/ \(\left(x-39\right)-21=0\)
\(\Rightarrow x-39=0+21=21\)
\(\Rightarrow x=21+39=60\)
c/ \(231+\left(312-x\right)=531\)
\(\Rightarrow312-x=531-231=300\)
\(\Rightarrow x=312-300=12\)
d/ \(53\cdot\left(9-x\right)=53\)
\(\Rightarrow9-x=\frac{53}{53}=1\)
\(\Rightarrow x=9-1=8\)
a) 124 + (118 - x) = 217
118 - x = 217 - 124
118 - x = 93
x = 118 - 93
x = 25
b) 156 - (x + 61) = 82
x + 61 = 156 - 82
x + 61 = 74
x = 74 - 61
x = 13
c) 219 - 7(x + 1) = 100
7(x + 1) = 219 - 100
7(x + 1) = 119
x + 1 = 119 : 7
x + 1 = 17
x = 17 - 1
x = 16
d) (3x - 6).3 = 3⁴
3x - 6 = 3⁴ : 3
3x - 6 = 3³
3x - 6 = 27
3x = 27 + 6
3x = 33
x = 33 : 3
x = 11
e) 231 - (x - 6) = 1339 : 13
231 - (x - 6) = 103
x - 6 = 231 - 103
x - 6 = 128
x = 128 + 6
x = 134
a) 124 + (118 - x) = 217
118 - x = 217 - 124
118 - x = 93
x = 118 - 93
x = 25
b) 156 - (x + 61) = 82
x + 61 = 156 - 82
x + 61 = 74
x = 74 - 61
x = 13
c) 219 - 7(x + 1) = 100
7(x + 1) = 219 - 100
7(x + 1) = 119
x + 1 = 119 : 7
x + 1 = 17
x = 17 - 1
x = 16
d) (3x - 6) . 3 = 34
(3x - 6) . 3 = 81
(3x - 6) = 81 : 3
(3x - 6) = 27
3x = 27 + 6
3x = 33
x = 33 : 3
x = 11
e) 231 - (x - 6) = 1339 : 13
231 - (x - 6) = 103
(x - 6) = 231 - 103
x - 6 = 128
x = 128 + 6
x = 134
a)0,12.X-2=4
=>0,12.X=4+2
=>0,12.X=6
=>X=6:0,12
=>X=50
b)231-(X-6)=1339:13
=>231-(X-6)=103
=>X-6=231-103
=>X-6=128
=>X=128+6
=>X=134
c)7,99.X+X.2+X:100=7,9
=>X.(7,99+2+1/100)=7,9
=>X.10=7,9
=>X=7,9:10
=>X=0,79
d)(14-X:6).7=84
=>14-X:6=84:7
=>14-X:6=12
=>X:6=14-12
=>X:6=2
=>X=2.6
=>X=12
Đáp án là C